Pengaruh Sales Promotion Dan Electronic Word Of Mouth (E-Wom) Terhadap Minat Beli Sepatu Dan Sandal Brand Geoff Max (Studi Kasus Mahasiswa Manajemen Unisma Angkatan 2021) - Ayodya, Muhammad Vigas Frasta; Widarko, Agus; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Sales Promotion and Electronic Word of Mouth (E-WOM) on Purchase Intention among Management students at Universitas Islam Malang (UNISMA) class of 2021. Using a quantitative approach with a survey method, data were collected from 82 respondents determined through purposive sampling. The analysis employed multiple linear regression with the assistance of SPSS software. The results indicate that Sales Promotion has a positive and significant effect on Purchase Intention, suggesting that promotional strategies such as discounts, cashback, flash sales, and bundling can effectively attract students to consider purchasing products. Similarly, E-WOM also shows a strong and significant effect on Purchase Intention, highlighting the importance of digital reviews, comments, and recommendations in shaping consumer trust and purchase decisions. Furthermore, the simultaneous test confirms that both variables together contribute significantly, explaining 85% of the variation in Purchase Intention. These findings emphasize that combining economic incentives with social validation through E-WOM creates a more effective marketing strategy, especially for young digital consumers like university students. Keywords: Sales Promotion, Electronic Word of Mouth, Purchase Intention, University Students